Training sheep for indirect calorimetry trials - Fonseca, Vinicius F. C. [UNESP]; Saraiva, Edilson P.; Maia, Alex S. C. [UNESP]; Melo Costa, Cintia Carol de [UNESP]; Santos, Severino Guilherme C. G. dos; Morais, Larissa K. C.; Fuller, Andrea; Chiquitelli Neto, Marcos [UNESP] (Elsevier B.V., 2019)
Training methods for animals are useful in experimental work, particularly for respirometry studies. Here we describe the training process for a hair coat sheep breed to be assessed in subsequent indirect calorimetry trials. Behavioral and physiological measurements were taken to determine if the training reduced the animals' fear reactions, mainly to restraint at the squeeze chute and use of a facial mask. Sixteen Morada Nova sheep with body mass of 32.6 +/- 1.8 kg and 2.8 +/- 0.9 years of age (+/- SD) were randomly chosen to undergo the training. The training was divided into three periods across 76 days that consisted of a gradual alteration of the environmental conditions required for the future indirect calorimetry tests. Results revealed that the training had positive or neutral effects on the ewes'physiological and behavioral performance. At the end of training we observed that the restraint and use of a facial mask did not change (P > 0.05) the respiratory rate of the ewes. Furthermore, all animals voluntarily accessed (P < 0.05) the squeeze chute, and the number of vocalizations and head shakes (P < 0.05) decreased across the training time. Temperament assessments also showed that the group of trained ewes perceived restraint and human presence as a less stressful (P < 0.05) situation than did those that had never experienced the training (i.e., naive ewes). We were able to detect less fearful ewes by examining the inter-individual behavioral responses using Principal Component analysis, and use them in subsequent calorimetry trials. Our results showed that the resting metabolic rate of similar-sized ewes differenced by less than 10%. In conclusion, this study described a training protocol that was able to habituate sheep to voluntarily access a squeeze chute and use a facial mask for up fifty minutes without apparent changes in behavioral or physiological responses.
Keywords: Energy metabolism; Human-Animal relationship; Fear response; Habituation; Positive reinforcement